The Role of Local Government in Developing Tourism Villages in Ponggok Village - Muhammad Jafar; Gimas Rahadyan; Agelica Ayu Santice Putri (HK-Publishing, 2026)
Abstract This study aims to analyze the role of the local government in the development of Ponggok Tourism Village in Klaten Regency. Tourism village development is one of the government's strategies to improve community welfare by optimizing local tourism-based potential. This study used a qualitative case study method to determine the government's role in developing Ponggok Tourism Village as a tourist destination. The results show that the local government's role in developing Ponggok Tourism Village has been implemented through various functions, namely as a regulator, facilitator, mentor, and evaluator. Based on role theory, the expectation indicator is realized through systematic tourism village development planning, gathering community aspirations, and formulating policies supported by various regional regulations. The norm indicator is reflected in the implementation of government duties in accordance with statutory provisions and community involvement in the tourism village development process. Furthermore, the behavioral indicator (performance) is seen in the success of Ponggok Village as an independent tourism village that is able to increase village income, develop Village-Owned Enterprises (BUMDes), and encourage community economic growth. The role assessment indicators (evaluation) are implemented through periodic assessment and evaluation mechanisms conducted by the local government and stakeholders regarding the development of tourism villages. However, this study also found that obstacles remain, particularly in infrastructure, environmental management, and improving tourism support facilities, which require further attention. Keywords: Role, Local Government, Tourism Village Development, Ponggok Village. Abstrak Penelitian ini bertujuan untuk menganalisis peran pemerintah daerah dalam pengembangan Desa Wisata Ponggok di Kabupaten Klaten. Pengembangan desa wisata merupakan salah satu strategi pemerintah untuk meningkatkan kesejahteraan masyarakat dengan mengoptimalkan potensi lokal berbasis pariwisata. Penelitian ini menggunakan metode studi kasus kualitatif untuk mengidentifikasi peran pemerintah dalam mengembangkan Desa Wisata Ponggok sebagai destinasi wisata. Hasil penelitian menunjukkan bahwa peran pemerintah daerah dalam pengembangan Desa Wisata Ponggok telah diwujudkan melalui berbagai fungsi, yaitu sebagai regulator, fasilitator, pembina, dan evaluator. Berdasarkan teori peran, indikator ekspektasi diwujudkan melalui perencanaan pengembangan desa wisata yang sistematis, penjaringan aspirasi masyarakat, serta perumusan kebijakan yang didukung oleh berbagai peraturan daerah. Indikator norma tercermin dalam pelaksanaan tugas pemerintah sesuai dengan ketentuan perundang-undangan dan pelibatan masyarakat dalam proses pengembangan desa wisata. Selanjutnya, indikator perilaku (kinerja) terlihat dari keberhasilan Desa Ponggok sebagai desa wisata mandiri yang mampu meningkatkan pendapatan desa, mengembangkan Badan Usaha Milik Desa (BUMDes), serta mendorong pertumbuhan ekonomi masyarakat. Indikator penilaian peran (evaluasi) dilaksanakan melalui mekanisme penilaian dan evaluasi berkala yang dilakukan oleh pemerintah daerah dan para pemangku kepentingan terkait pengembangan desa wisata. Namun, penelitian ini juga menemukan adanya hambatan, khususnya pada aspek infrastruktur, pengelolaan lingkungan, dan peningkatan fasilitas pendukung pariwisata, yang memerlukan perhatian lebih lanjut. Kata kunci: Peran, Pemerintah Daerah, Pengembangan Desa Wisata, Desa Ponggok.